1993
DOI: 10.1007/bf00298722
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone involvement in the regulation of tartrate-resistant acid phosphatase-positive cells that are active in cartilage and bone resorption

Abstract: Young male Sprague-Dawley rats (5-7 weeks old, 80-120 g) were hypophysectomized (HX) and maintained on thyroxin and dexamethasone replacement therapies. Ten days after surgery, some HX rats received a single injection of human growth hormone (hGH), and others five daily injections of hGH. Tartrate-resistant acid phosphatase (TRAP) histochemistry was employed in order to evaluate the number of cells of resorptive potential in the metaphyseal bone of the proximal tibiae of HX rats and was compared with normal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…TRAP, a lytic enzyme important for dissolving mineral in bone, is differentially expressed both temporally and spatially along the frontal bones during eye migration (Saele et al 2006). In mammals, GH and IGF-I stimulate bone resorption (Guicheux et al 1998) and stimulate TRAP-positive cells (Gevers et al 1996;Lewinson et al 1993). Although no detailed information exists about the role of GH and IGF-I in bone proliferation and resorption in fish, both hormones appear to be involved in seasonal vertebral growth in juvenile Atlantic salmon (Salmo salar; Wargelius et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…TRAP, a lytic enzyme important for dissolving mineral in bone, is differentially expressed both temporally and spatially along the frontal bones during eye migration (Saele et al 2006). In mammals, GH and IGF-I stimulate bone resorption (Guicheux et al 1998) and stimulate TRAP-positive cells (Gevers et al 1996;Lewinson et al 1993). Although no detailed information exists about the role of GH and IGF-I in bone proliferation and resorption in fish, both hormones appear to be involved in seasonal vertebral growth in juvenile Atlantic salmon (Salmo salar; Wargelius et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the net bone mass and bone density were not completely restored to the level of the age-matched intact animals. In a similar study, Lewinson et al [33] found out that the number of osteoclasts in the metaphyseal bone of the proximal tibia of the HX rat was increased by GH, thereby increasing bone resorption. Wang et al [34], using pQCT densitometry, demonstrated that GH completely restored cortical bone in vertebra; however, both histomorphometric and pQCT measurements demonstrated that GH had no significant effect on the vertebral cancellous bone of aged, ovariectomized, osteopenic rats.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, GH was shown to have specific effects on growth plate cells, as already reviewed (20). In a rat model, GH enhances the mobilization of tartrate-resistant acid phosphatase-positive osteoclasts that are active in cartilage and bone resorption in enchondral osteogenesis (21). Whereas the primary ossification centers of long bones are well ossified at birth, the carpal cuboid bones of the hands portray a unique opportunity to observe primary ossification centers in their making.…”
Section: Discussionmentioning
confidence: 99%